Follower Strengths-based Leadership and Follower Innovative Behavior : The Roles of Core Self-evaluations and Psychological Well-being - Ding, He.; Yu, Enhai (Madrid : Colegio Oficial de Psicólogos de Madrid, 2020)
This study investigated the relationship between followers' strengths-based leadership (FSBL) and innovative behavior and the mediating role of psychological well-being (PWB) and the moderating role of core self-evaluations (CSE) in the relationship. In order to test our hypotheses data from Chinese enterprises were used. Results of multiple linear regression and bootstrapping analyses showed that FSBL is positively related to follower innovative behavior and PWB significantly mediates the FSBL-innovative behavior relationship. In addition, CSE negatively moderates the direct effect of FSBL on PWB and the indirect effect of FSBL on innovative behavior via PWB such that the direct effect of FSBL on PWB and the indirect effect of FSBL on innovative behavior via PWB will be stronger for followers with a low level of CSE rather than for followers with a high level of CSE. Theoretical implications, practical implications and future research were also discussed.
En inglés; resúmenes en español e inglés.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Descripción basada en Journal of work and organizational psychology, vol. 36, n. 2 (August 2020), P. 103-110.
Recurso electrónico. Santa Fe, Arg.: elibro, 2024. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Autoevaluaciones principales; Bienestar psicológico.; Comportamiento innovador; Liderazgo sustentado en las fortalezas de los subordinados; Artículos electrónicos.